Implementasi Metode Bermain Peran Dengan Model Kooperatif Tipe Stad Untuk Meningkatkan Kemampuan Berbahasa Jawa Krama - Septiyani Zahrotun Nihmah; Septian Zuhri Kuncoro; Diana Ermawati (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to improve polite language skills in Javanese language learning through the role playing method with the STAD type cooperative model for class II students at SD Negeri 04 Karangbener, even semester of the 2024/2025 academic year in learning local Javanese content with Javanese krama language material. Researchers used classroom action research with two cycles. The cycle stages are the planning, implementation, observation and reflection stages. The target was carried out on 18 class II students at SDN 04 Karangbener for the 2024/2025 academic year. Obtaining data in the form of observation sheets of learning activities and formative tests. In obtaining the results of the analysis, there was an increase in student learning outcomes in cycle I to cycle II, namely cycle I 83.33% and cycle II 100%. It was concluded in the classroom action research that had been carried out that the implementation of the role playing method with the STAD type cooperative learning model was able to improve students' ability to use Javanese language skills in class II of SD Negeri 04 Karangbener for the 2024/2025 academic year with the STAD type cooperative learning model and the role playing method. can be used in classroom learning to improve student learning outcomes.